Permainan Edukatif Berbasis Kartu untuk Meningkatkan Pemahaman Matematika Siswa SD - Siti Solihah, Ade Putri; Nur Malihah, Chelly; Sapta Ramadan, Candra (Papanda Publisher, 2025)
Mathematics is often considered difficult by students so that the low understanding of mathematical concepts in elementary schools is still a common problem that occurs in learning. The alternative thing that can be done by teachers is by developing innovations in learning, one of which is using card-based educational games. This review aims to examine various studies on the effectiveness of card games in improving students' understanding of mathematics in elementary schools. The method used in this article is a systematic literature study of 10 articles published between 2020 and 2025 obtained from Google scholar. The inclusion criteria include articles that are in line with card games in primary school mathematics learning and have a focus on concept improvement. The results of the review show that the use of card games such as question cards and number cards can increase student engagement in learning. In addition, students are able to understand abstract math concepts and can create a fun learning atmosphere. Thus, card-based educational games are proven to be an effective strategy in improving students' mathematical understanding in primary schools and can be implemented in learning.